Level of Online Game Addiction on Adolescents - Tri Prayuda Dwipha Surbakti; Imas Rafiyah; Setiawan Setiawan (Journal of Nursing Care, 2022)
Online game is increasingly popular entertainment for all ages, especially on adolescents. Previous study had shown that the most internet users in Indonesia are adolescents and playing online game is the most activities frequently accessed by adolescents. Previous research also showed that online game addiction among Indonesian students was estimated at 10,15%. This study aimed to identify the level of online game addiction in adolescents. This research was in form of quantitative descriptive. The study population was all students of class X dan XI who obtained students from screening results and have met certain criteria with total of 241 people. The population and sample criteria in this study were adolescents who played online games for at least 6 months starting from the first time playing online game. The sampling technique used was total sampling, that all members of the population were used as sample. Data was collected within a month using The Indonesian Online Game Addiction Questionnaire and data obtained directly through google form. The result of the study was analyzed by univariate analysis then grouped into groups of respondents with a score of 7-13 no addiction, 14-21 on mild level of addiction, and 22-35 on high level of addiction. Base on the data analysis, the result of this study showed that almost all respondents were male (87,1%) with duration of ≤ 3 hours/day atau ≤ 21 hours/week to play online game (69,3%). Nearly half of respondents were addicted at a mild level (49,8%) and partially at a high level (10,8%). The conclusion of this study was that the level of addiction in adolescent was dominated at a mild level. The suggestion for school and school health nurses are to collaborate in prevention and treatment efforts by providing education about time management and the dangers of online game addiction to students.